Wind-tunnel Experiments and Trajectory Analyses for Five Nonspinning Soccer Balls. (2016) - Goff, John Eric; Hobson, Chad Michael; Asai, Takeshi; Hong, Sungchan
Abstract: We report drag, side, and lift coefficients for two orientations of five non-spinning soccer balls (Brazuca, Cafusa, Jabulani, Teamgeist 2, and Vantaggio), measured using a wind tunnel. The air's speed range was 7 m/s to 35 m/s, covering most of the speeds of kicked soccer balls in real games. Trajectory analyses make use of our aerodynamic wind-tunnel data and show that the five balls we tested behave differently while in flight. We also show that in some cases, changing ball orientation leads to a significant change in flight trajectory. Turning off side and lift forces alter ranges and lateral deflections as fractions of ranges in excess of 10% for some balls. Because we have only two orientations for non-spinning balls, the work we present here is just the preliminary investigation of a much larger project in which we hope to have aerodynamic data for many more ball orientations.